The Role of Government, Financial Literacy and Inclusion on the Financial Peformance of MSMEs in Malang City - Dwi Ekasari Harmadji; Rachma Yuliana; Rosyid Arifin; Ayu Kemala Putri (Jurnal Keuangan dan Perbankan, 2022)
Micro, Small, and Medium Enterprises (MSMEs) in Malang City, East Java Province, are important economic assets because they reduce unemployment and poverty. The number of MSMEs units in Malang City has increased, but their performance has decreased during the Covid-19 pandemic. This situation correlates with financial literacy, the role of Government, and financial inclusion. This study aims to determine the factors that influence the financial performance of MSMEs in Malang City during the COVID-19 pandemic, which includes financial inclusion as a moderating variable for the influence of financial literacy and the role of the Government. This research is quantitative, and data is obtained through questionnaires. Respondents to this research questionnaire were 129 MSMEs in Malang City. The results of the analysis are: first, the role of the Government has a positive effect on the financial performance of MSMEs; second, financial literacy has a positive impact on the financial performance of MSMEs; third, financial inclusion moderates the role of the Government and financial literacy on the financial performance of MSMEs in Malang City. This research contributes to collaboration on the part of Government, financial literacy, and financial inclusion to improve the financial performance of MSMEs.